Financial Advice and Household Financial Portfolios - Sarah Brown; Alessandro Bucciol; Alberto Montagnoli; Karl Taylor (Institute of Labor Economics (IZA), 2021)
We investigate the role of financial advice in shaping the composition of household portfolios in Great Britain. Advice is associated with a reallocation of wealth away from real estate and towards bonds and stocks, especially when households seek financial advice "for investments". Having a consultation with a stockbroker has a particularly large effect on the portfolio share in stocks. However, even free financial advice has a positive effect on the shares in bonds and stocks, compared to not receiving advice. Finally, we find a positive association between alternative measures of portfolio risk and the composition of the portfolio, whilst accounting for financial advice.
Keywords: D81; G11; D14; 330; financial advice; financial risk; household financial portfolios